Periodic nanowire arrays with alternating compositions and structures fabricated using a simultaneous nanowire formation step. Issue 43 (25th October 2021) - Burg, Ofer; Sanguramath, Rajashekharayya A.; Michman, Elisheva; Eren, Noga; Popov, Inna; Shenhar, Roy
Abstract : The spatial location of cylindrical domains within thin block copolymer films was used to selectively modify similar domains with different materials. Subsequent plasma treatment led to nanowire arrays with alternating compositions or nanostructures. Abstract : Arrays of alternating metallic nanostructures present hybrid properties, which are useful for applications in photonics and catalysis. Block copolymer films provide versatile templates for fabricating periodic arrays of nanowires. Yet, creating arrays with alternating compositions or structures requires different modifications of domains of the same kind. By controlling the penetration depth of metal precursors into the film we were able to impregnate different layers of copolymer cylinders with different metals. Capitalizing on the hexagonal packing of the cylinders led to simultaneous formation of nanowires with alternating compositions and periodic arrangement on the substrate after plasma etching. Selective deposition of nanoparticles on the film enabled creating alternating bare and decorated nanowires, as well as trimetallic nanowire arrays.